2021
DOI: 10.1021/acsnano.1c01039
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Manipulation of Individual Atomic-Scale Defects for Boosting Thermoelectric Performances in Artificially Controlled Bi2Te3 Films

Abstract: The manipulation of individual intrinsic point defects is crucial for boosting the thermoelectric performances of n-Bi2Te3-based thermoelectric films, but was not achieved in previous studies. In this work, we realize the independent manipulation of Te vacancies VTe and antisite defects of TeBi and BiTe in molecular beam epitaxially grown n-Bi2Te3 films, which is directly monitored by a scanning tunneling microscope. By virtue of introducing dominant TeBi antisites, the n-Bi2Te3 film can achieve the state-of-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 44 publications
(110 reference statements)
3
50
0
Order By: Relevance
“…First, under a suitable T sub and a low growth rate, Bi 2 Te 3 ‐based thin films can be grown stably by the process of layer‐by‐layer growth and their microstructure is typified by the (00 l ) orientation. As documented by the MBE‐grown films in our laboratory and elsewhere, [ 88,100,101,105 ] the films grown under stable conditions are evidenced by the strictly c ‐oriented growth of QLs (determined by high‐resolution transmission electron microscope measurements) and by the sequentially stacked QLs on the surface (observed via atomic force microscope), see the bottom panel in Figure 2. Second, the (0 1 5) preferential orientation is usually present in Bi 2 Te 3 ‐based thin films that were grown under unstable conditions, for example, under a rather low T sub and at too high growth rates, see the middle panel in Figure 2.…”
Section: Fabrication and Te Properties Of Bi2te3‐based Filmsmentioning
confidence: 68%
See 2 more Smart Citations
“…First, under a suitable T sub and a low growth rate, Bi 2 Te 3 ‐based thin films can be grown stably by the process of layer‐by‐layer growth and their microstructure is typified by the (00 l ) orientation. As documented by the MBE‐grown films in our laboratory and elsewhere, [ 88,100,101,105 ] the films grown under stable conditions are evidenced by the strictly c ‐oriented growth of QLs (determined by high‐resolution transmission electron microscope measurements) and by the sequentially stacked QLs on the surface (observed via atomic force microscope), see the bottom panel in Figure 2. Second, the (0 1 5) preferential orientation is usually present in Bi 2 Te 3 ‐based thin films that were grown under unstable conditions, for example, under a rather low T sub and at too high growth rates, see the middle panel in Figure 2.…”
Section: Fabrication and Te Properties Of Bi2te3‐based Filmsmentioning
confidence: 68%
“…As a result, as shown in Figure 4C, the band bending and the built-in electric field introduce extra scattering for the mobile charge carriers, and this leads to an obviously degraded carrier mobility in n-type Bi 2 Te 3 films. Further studies by Zhang et al [101,105] have confirmed the above conjecture by finely tuning the intrinsic defects. N-type Bi 2 Te 3 films with n-type antisites Te Bi as the dominant atomic defects, instead of V Te and Bi Te defects, showed improved carrier mobility of above 80 cm 2 V -1 s -1 , notably higher than the common values of μ ≤ 50 cm 2 V -1 s -1 .…”
Section: Atomic Defect Engineeringmentioning
confidence: 70%
See 1 more Smart Citation
“…[34][35][36][37] Therefore, there has been much work carried out on Bi 2 Te 3 films. [38][39][40][41][42][43][44][45] In regards to utilizing the enhancement methods of CNT compositing and porosity, which we have particularly focused on in this work, the thermal conductivity of Bi 0.4 Te 3 Sb 1.6 films decreases to 0.25 W m −1 K −1 by compositing porosity, resulting in the increase of ZT. [46] The TE properties of Bi 2 Te 3 films can also be enhanced by compositing carbon allotropes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with its bulk counterparts, nanostructured Bi 2 Te 3 film provides promising possibilities for enhanced TE properties and potential applications in micro/nanoelectromechanical systems (MEMS/NEMS) TE device [8]. The thermoelectric performance of Bi 2 Te 3 can be optimized by adjusting the (00l) orientation [9,10], pores [9,11], nanosheet boundary [12,13], and the intrinsic defects [14,15]. In addition, constructing a heterogeneous interface is also one of the effective methods to optimize the thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%